2021
DOI: 10.1080/21655979.2021.1938498
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of a three-gene signature in predicting diagnosis in patients with myocardial infarction

Abstract: In this study, we evaluated the diagnostic value of key genes in myocardial infarction (MI) based on data from the Gene Expression Omnibus (GEO) database. We used data from GSE66360 to identify a set of significant differentially expressed genes (DEGs) between MI and healthy controls. Logistic regression, least absolute shrinkage and selection operator (LASSO) regression, support vector machine recursive feature elimination (SVM-RFE), and SignalP 3.0 server were used to identify the potential role of genes in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Further, we used the LASSO regression and SVM-RFE algorithm to screen for the four genes. SVM-RFE is a powerful feature selection algorithm [ 18 ] that has been used in the bioinformatics research of cardiovascular diseases [ 14 ], tumours [ 19 ], and Alzheimer's disease [ 20 ]. When there are many features, SVM-RFE is a good choice to avoid overfitting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, we used the LASSO regression and SVM-RFE algorithm to screen for the four genes. SVM-RFE is a powerful feature selection algorithm [ 18 ] that has been used in the bioinformatics research of cardiovascular diseases [ 14 ], tumours [ 19 ], and Alzheimer's disease [ 20 ]. When there are many features, SVM-RFE is a good choice to avoid overfitting.…”
Section: Discussionmentioning
confidence: 99%
“…The genes obtained by LASSO and SVM-RFE were intersected to obtain a diagnosis-related gene signature set associated with paediatric sepsis. The receiver operating characteristic (ROC) curve, C-index, and principal component analysis (PCA) were used to evaluate the diagnostic value of the gene signatures [ 13 , 14 ]. Further, “ROCR,” “Hmisc,” and “ggplot2” packages were used by ROC, C index, and PCA, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Then, LASSO logistic regression and SVM-RFE were used to select the most significant characteristic genes in this study. The subset intersection of the genes screened was also used to screen feature genes using multivariate logistic regression, with the criterion of p < 0.05 [ 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Based on the gene expression profiling data of AMI, Bowers’ LAPP method [ 14 ] was used to construct a first-order logic network (also known as a directed network). Using NCCM, 17 differential control capability genes (DCCGs) related to AMI were identified, 14 of which ( NR4A3 [ 15 ], THBS1 [ 16 , 17 ], CXCL3 [ 18 ], ITLN1 [ 19 , 20 ], CLEC4D [ 21 ], LRG1 [ 22 ], IRAK3 [ 23 , 24 ], HBEGF [ 25 ], MMP9 [ 26 , 27 ], NLRP3 [ 28 , 29 , 30 ], EDN1 [ 31 ], VNN3 [ 24 ], and PDK4 [ 32 ]) were significantly related to the growth, proliferation, and repair of AMI/MI cells, and BCL6 [ 33 ] was indirectly related. The enrichment analysis of DCCGs showed that AMI was significantly related to the positive regulation of smooth muscle cell proliferation and the regulation of cytokine production involved in the immune response.…”
Section: Introductionmentioning
confidence: 99%